A construção da relação homem, sociedade e natureza: a percepção ambiental dos moradores da comunidade rural Saltinho do Rio Sarandi no município de Realeza – PR - Grisa, Jaqueline Gomes Demarchi (2020)
The relationship between man and nature is changing according to the utilitarian, conservationist, cultural and symbolic meaning in which he is inserted. With this, in the capitalist society it is noticed the intensification of the environmental consequences that has been happening with this utilitarian relationship between man and nature. Capitalism gained strength with the expansion of the Industrial Revolution, which urbanization took on very sharp rhythms. With all this urbanization, cities often do not keep pace with the growth, thus generating a housing density. With more valued spaces, families with low purchasing power need to look for places with values accessible to their conditions of need for decent housing. In this sense, the general objective of the research is to analyze the environmental perception of the residents who live on the banks of the Sarandi River of the Saltinho Rural Community in the Municipality of Realeza – PR, aiming at the identification and understanding of the possible relations they have with the river, on the conservation of water and the right to housing as a condition of dignified life. The methodology applied for this research was the dialectical method. Taking qualitative research as an approach. We opted for this work, the exploratory research method, using field research. The applied technique was structured interview. Therefore, the research seeks to expand the knowledge of the relationship between man, society and nature, in order to understand the consequences of capitalist society on the social being in relation to the environment, and through the characterization of the studied population and the study carried out to assist in the possible formulations of actions and projects for the conservation of this River, as well as public policies aimed at planning and integrated actions to promote the right to sustainable development in this rural and surrounding area.